Implementation of the HACCP tool and microbiological quality of agbelima production on a site in South Benin - AGASSOUNON DJIKPO TCHIBOZO, Micheline (My University, 2021)
The Hazard Analysis and Critical Control Point system (HACCP) is a scientific and systematic approach to identify hazards and provide measures for their control to ensure food safety. Thus, to ensure that the quality of agbélima, a product derived from cassava is taken into consideration during processing, the HACCP system has been applied to improve both the quality and the safety of that product. The methodology used for the implementation of the quality approach on the chain of production of agbelima in South Benin is summarized by a survey for the analysis of the context and the environment of agbelima production, the hazard analysis and the determination of the critical points related to the production of agbelima, the realization of the model of the quality assurance system (HACCP) and the verification of the effectiveness of the system implemented. The hazard analysis was carried out according to the raw, material, labor, equipment, environment and method. The elaboration of the HACCP theorical model was carried out according to twelve classic steps. The HACCP system is implemented on the production site. Before and after the implementation of the system, microbiological analysis on eighteen samples of agbelima were carried out. The results of the hazard analysis indicate that hazards exist at all stages of agbelima production. The application of the HACCP theorical model resulted in the detection of 6 Critical Control Points (CCPs) throughout the production chain. These are the reception of the raw material, washing, grinding, pressing, fine milling, and packaging. The analysis reveals that all eighteen samples of agbelima analysed before the implementation of the approach are not in conformity with the regulatory requirements. However, after the application of the system, a varying reduction from 93.49 % to 100 % was noted for microorganisms such as: Total Mesophilic Flora, Lactic Flora, Yeasts and Moulds and Sulfito Reducing Anaerobes, ColiformsThermotolerant, E. coli, Staphylococci and Salmonella in agbelima samples. Compliance with the implementation guide is 77.5 % in relation to twelve steps of the system application. Improvements are needed on the records and their effective updating to maintain the level of quality of this product
Keywords: cassava; agbelima; HACCP; quality; Benin.